ANALISIS SWOT PADA STRATEGI PEMASARAN: MEMBANGUN BISNIS YANG BERDAYA SAING (STUDI KASUS UMKM THAI TEA CE ES) - Muthia Rahma Putri Dahlia; Michael Farezi; Nia Febriyanti; Indah Noviyanti (Politeknik Bisnis Indonesia, 2024)
In this era of rapid technological development, it places demands on micro, small, and medium enterprises (MSMEs) to be able to provide innovation and creativity with the aim of creating competitiveness in the businesses they run. This article will provide critical research through the SWOT analysis process along with marketing and competitive strategies for Thai Tea Ce Es MSMEs as a case study. This research will focus on the sales analysis of Thai Tea Ce Es using SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of Thai Tea Ce Es MSMEs. Apart from that, this research also uses marketing and competitive strategies to improve brand reputation, take advantage of market growth, build relationships with customers, and design a structured business plan. This research was conducted using descriptive research with a qualitative approach as well as observation methods and in-depth interviews with the owner of Thai Tea Ce Es. By implementing marketing and competition strategies assisted by SWOT analysis on business, it will certainly have a positive impact because it can increase competitiveness and also create business resilience for Thai Tea Ce Es MSMEs in facing market changes that continue to develop.